2018
DOI: 10.3144/expresspolymlett.2018.85
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous microencapsulation of geraniol by zein

Abstract: Geraniol was successfully micro-encapsulated with zein in a one-step phase separation process in which the zein and geraniol were both initially dissolved in a water-ethanol mixture. Microcapsules were only formed at geraniol-to-zein mass ratios above unity. This is ascribed to the relative solubility of the oil and protein in the solvent at the point of incipient phase separation: The geraniol must phase separate first before zein precipitation commences. The resultant oil droplets subsequently provide the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
(37 reference statements)
2
1
0
Order By: Relevance
“…This particle size is similar to that measured for many essential oil microcapsules [13,45,46]. The image was normally distributed and relatively narrow, clarifying that the microcapsules prepared under optimal process conditions were of uniform size, which was consistent with the results in the literature [47].…”
Section: Morphology and Particle Size Distribution Of Cmssupporting
confidence: 89%
See 1 more Smart Citation
“…This particle size is similar to that measured for many essential oil microcapsules [13,45,46]. The image was normally distributed and relatively narrow, clarifying that the microcapsules prepared under optimal process conditions were of uniform size, which was consistent with the results in the literature [47].…”
Section: Morphology and Particle Size Distribution Of Cmssupporting
confidence: 89%
“…This particle size is similar to that measured for many essential oil microcapsules [13,45,46]. The image was normally distributed and relatively narrow, clarifying that the microcapsules prepared under optimal process conditions were of uniform size, which was consistent with the results in the literature [47]. The significantly larger particle size compared to the freeze-dried dry capsule is mainly because the wall materials prepared from the microcapsules were hydrophilic polymers with strong swelling properties [48], which also indicated that they can be easily redispersed into the aqueous media.…”
Section: Morphology and Particle Size Distribution Of Cmssupporting
confidence: 89%
“…Once the correct temperature range is identified, it is possible to estimate the mass of the encapsulated active (active in capsules) as the weight loss of the capsules in that temperature range. The encapsulation efficiency (EE) can be defined as the mass of encapsulated active material compared to the mass of the active material added to the initial formulation [23], as reported in Equation (1) below: EE = active in capsules total active…”
Section: Methodsmentioning
confidence: 99%